Dermatopathological characteristics of dermatofibromas from dermatoscopic clues. (1st July 2019) - Genc, Yeser; Akay, Bengu Nisa; Okcu Heper, Aylin; Rosendahl, Cliff; Erdem, Cengizhan
Abstract: Background: Several types of dermatofibroma (DF) have been identified dermatopathologically and with dermatoscopic correlation, the dermatopathology has been predictable in limited studies so far. We identify DFs with specific dermatoscopic structures and determine the respective dermatopathological correlates. Methods: Dermatoscopic and dermatopathologic correlation of 403 DFs were assessed. A pattern analysis algorithm was used for the dermatoscopic evaluation, each lesion being evaluated according to 10 dermatoscopic patterns with further subdivision of the atypical subtype according and their dermatoscopic similarities to other defined skin lesions. Results: Dermatoscopic pattern analysis showed typical patterns in 83.4% of DFs with atypical patterns in 16.6%. We classified the atypical DFs according to their dermatoscopic similarity to certain lesions: Melanoma‐like 2.7%, basal cell carcinoma‐like 0.7%, keratoacanthoma‐like 0.5%, seborrheic keratosis‐like 2.7%; nevus‐like 1.5%; nevus sebaceous‐like 0.9%; xanthogranuloma‐like 0.5%; pyogenic granuloma‐like 0.5%; and spitzoid 6.5%. Dermatopathologically 12 subtypes of DFs were identified. It was found that the most common pattern found in fibrocollagenous DFs was the typical pattern with peripheral reticular lines and central white structureless area (32.9%) whereas non‐fibrocollagenous types were more likely to have atypical patterns (65.1%). Conclusions: Our study resulted in new conclusions while supporting some previous findings. The fact that the pathogenesis of DF involves a reactive inflammatory process with fibrosis is likely to have diverse effects on dermatoscopic morphology. If atypical dermatoscopic patterns are identified in suspected DF, excisional biopsy may be prudent.